Об’єктивні та суб’єктивні чинники соціальної та етнорелігійної структури населення Волинського воєводства у 20-30 роках XX століття - Булавіна, Світлана Євгенівна; Bulavina, Svitlana Ye. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті проаналізовано об'єктивні та суб'єктивні чинники соціальної та етнонаціональної структури населення Волинського воєводства у 20-30-х роках ХХ ст., підкреслено, що серед представників 34 національностей, які проживають на території воєводства, переважали українці та православні віряни, наголошено, що в міжвоєнне двадцятиріччя чітко окресленою соціальною групою стає волинська інтелігенція, зокрема педагогічні кадри з притаманними їм характерними рисами, психологією, поведінкою.

The article analyzes the objective and subjective factors of social and ethno-religious structure of the Volyn Voivodeship population in 20-30-ies of the XX-th century. The emphasis is laid on the fact that Volyn remained agrarian area with underdeveloped infrastructure and the agricultural policy of the Polish authorities was aimed at the colonization of the region, creation of the Polish households as a kind of social support of the new regime. It has been emphasized that Ukrainians and Orthodox believers dominated among the 34 ethnic groups living in the Voivodeship. In the two interwar decades Volynian intelligentsia had become clearly defined social group, mainly represented by teaching staff with their typical characteristic features, psychology and behavior.
Objective and Subjective Factors of Social and Ethno-Religious Structure of the Volyn Voivodeship Population in 20-30-ies of the XX-th Century
Keywords: Волинське воєводство; об'єктивні та суб'єктивні чинники; православні віряни; волинська інтелігенція; Volyn Voivodeship; the objective and subjective factors; the Orthodox believers; Volynian intellectuals